Indonesia’s Non-Military Threats Dynamics: A Philosophical Perspective - Rahayu, Liska; Sihombing, Desi Natalia; Santoso, Puguh (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
This study aims to provide a novel philosophical analysis of the non-military threats facing Indonesia, grounded in an examination of their ontological nature, epistemological understanding, and axiological value implications. Amidst an increasingly complex global security landscape, non-military challenges like pandemics, climate change, cyber-attacks, and terrorism have emerged as critical concerns. This study employs a descriptive qualitative methodology and thematic analysis to comprehensively explore and understand the multifaceted dynamics of the non-military threats confronting Indonesia. The research findings depict that through an ontological lens, the research categorizes Indonesia's diverse non-military threats into three forms: the ideational synthesis of socio-political and technological factors (idealism); empirically observable phenomena like natural disasters and disease outbreaks (materialism); and existential risks integrating conceptual and physical elements like radicalism and separatism (dualism). Epistemologically, comprehensive data acquisition from varied sources, coupled with interdisciplinary analytical frameworks involving experts, government, and community stakeholders, enables contextually grounded threat assessments and mitigation policies responsive to evolving conditions. Axiologically, ethical principles of human dignity, social justice, and environmental stewardship rooted in Indonesian cultural values must anchor decision-making processes. The study recommends refining frameworks to better understand diverse threats, improving processes for collecting and analyzing data, incorporating ethical considerations into policy development, fostering interdisciplinary collaboration, and integrating local wisdom into defense strategies for enhanced resilience at both community and national levels.